Global challenges and regulatory strategies to fintech - GURREA-MARTINEZ, Aurelio (Institutional Knowledge at Singapore Management University, 2020)
The rise of new technologies has changed the operation, regulation and supervision of financial markets, bringing new challenges and opportunities for consumers, regulators, and financial institutions. This Article seeks to explore the most common regulatory strategies used by financial regulators around the world to address the challenges associated with the rise of fintech. These strategies include the imposition of bans, regulatory passivity, adoption of new legislation, permission on a case by case basis, and more interactive approaches such as innovation offices, accelerators and sandboxes. This Article argues that the adoption and desirability of each regulatory approach will depend on a variety of country-specific factors, including the goals and priorities of the regulator and the particular features of a country. Thefore, there are no one-size-fits-all solutions that can be suggested to promote financial innovation and effectively address the challenges generated by the rise of new technologies in the financial services industry.